Inner-shell photodetachment from Ni−: A giant Feshbach resonance - Dumitriu, I.; Bilodeau, R. C.; Gorczyca, T. W.; Walter, C. W.; Gibson, N. D.; Rolles, D.; Pešić, Z. D.; Aguilar, A.; Berrah, N. (My University, 2017)
Inner-shell photodetachment from Ni−([Ar]3d94s2) leading to Ni+,Ni2+, and Ni3+ ion production was studied near and above the 3p excitation region, in the 60–90 eV photon energy range, using a merged ion-photon beam technique. The absolute photodetachment cross section of Ni− leading to Ni+ ion production was measured. The 3p→3d photoexcitation in Ni− gives rise to a giant Feshbach resonance. In the near-threshold region, a Fano profile, modified by a Wigner s-wave (l=0) threshold law, accurately fits the Ni− single-photodetachment cross section. A lower-order R-matrix calculation shows overall agreement with essential features of the experimental data, confirming the nature of the strong, asymmetric Fano profile of the giant 3p→3d photoexcitation-autodetachment resonance in Ni−.